In vitro phagocytosis of Candida albicans by peritoneal mouse macrophages. - Evron, R (1980)
The ability of sensitized mouse peritoneal macrophages to phagocytose and inhibit Candida albicans was studied in an in vitro system. Mice were sensitized to C. albicans by intraperitoneal infection with viable organisms or by intracutaneous injection of heat-inactivated cells in Freund complete adjuvant. Development of delayed hypersensitivity to C. albicans was evaluated by footpad tests with cytoplasmic and cell wall antigens as well as by macrophage migration inhibition by these antigens and by whole heat-inactivated cells. Inhibition of macrophage migration by heat-inactivated cells was significantly greater when the mice were sensitized by viable organisms. The macrophages from these mice were also larger and showed a greaer ability to inhibit germ tube production by phagocytosed yeasts. This suggests that macrophages may play a protective role in infection by C. albicans.